2011
DOI: 10.1213/ane.0b013e31821e974f
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pulsed Radiofrequency Currents to Rat Dorsal Root Ganglia Modulates Nerve Injury–Induced Tactile Allodynia

Abstract: Background Application of pulsed radiofrequency (PRF) currents to the dorsal root ganglia (DRG) has been reported to produce relief from certain pain states without causing thermal ablation. In this study, we examined the direct correlation between PRF application to DRG associated with spinal nerve injury and reversal of injury-induced behavioral hypersensitivity in a rat neuropathic pain model. Methods Neuropathic lesioning was performed via left L5 spinal nerve ligation on male adult Sprague-Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 42 publications
3
46
1
Order By: Relevance
“…Main features of in vivo studies are shown in Table , divided by the type of stimulation in PRF stimulation group and EFS group . In all in vivo studies, SD rats weighing from 149 to 350 g were used.…”
Section: Resultsmentioning
confidence: 99%
“…Main features of in vivo studies are shown in Table , divided by the type of stimulation in PRF stimulation group and EFS group . In all in vivo studies, SD rats weighing from 149 to 350 g were used.…”
Section: Resultsmentioning
confidence: 99%
“…Four mammalian HCN channels have been cloned, HCN1-4, and subsequent studies have demonstrated widespread expression of all isoforms in both the PNS and CNS (Ludwig et al 1998). Changes in DRG neurons, the primary sensory neurons in peripheral pain processing, are crucial for the development of neuropathic pain (Chung et al 2002;Sluijter 2005;Wan 2008;Perret et al 2011). The present study revealed differential expression of HCN channel subtypes in DRG neurons, with HCN1 expressed mainly on the plasma membrane of large and medium-sized neurons, and HCN2 mainly in the cytoplasm of medium and small-sized neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PRF also reduces nociceptive responses in animal models. Tanaka et al demonstrated that PRF of the rat sciatic nerve significantly reduces mechano-allodynia induced by resiniferatoxin (Tanaka et al 2010), Aksu et al found that PRF significantly decreases mechanohyperalgesia in rabbits after tight ligation of the sciatic nerve (Aksu et al 2010), and Perret et al reported that PRF to the DRG decreases allodynia in rats with chronic constriction injury (CCI) to the L5 spinal nerve (Perret et al 2011). In rats with L5 spinal nerve ligation (SNL), Park et al found that PRF decreases mechanohypersensitivity (Park et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental neuropathic pain models show the pain-relieving effect of PRF on mechanical hypersensitivity, and sometimes on thermal allodynia [79][80][81][82][83][84] (Table 1). …”
Section: Behavioral Studiesmentioning
confidence: 99%